From Welfare to Work: Evaluating a Proposed Tax and Benefit Reform Targeted at Single Mothers in Sweden - Lennart Flood; Elina Pylkkänen; Roger Wahlberg (Institute for the Study of Labor (IZA), 2003)
In this paper we propose a tax and benefit reform to increase the working hours and to decrease the welfare participation of single mothers in Sweden. We have access to highquality tax and income data, and use a detailed tax-benefit program to generate precise budget-sets. We formulate and estimate a structural, static model of labor supply and welfare participation. The results suggest that labor supply among single mother households in Sweden is quite elastic, and that there is self-selection into welfare. The proposed reform would generate welfare-gains for virtually everyone in the sample, yet would be revenue neutral.
Keywords: I38; J22; 330; single mothers; labor supply; welfare participation; tax and benefit reform; Alleinerziehende; Arbeitsangebot; Sozialhilfe; Steuerreform; Sozialreform; Schweden